2019
DOI: 10.1111/1365-2745.13149
|View full text |Cite
|
Sign up to set email alerts
|

Divergent responses to climate change and disturbance drive recruitment patterns underlying latitudinal shifts of tree species

Abstract: Climate change is expected to result in a reorganization of the continental distribution of tree species. Recent shifts in distribution patterns have been reported, but it is not always clear how climate change influences these patterns locally, especially in relation to other disturbances. We investigated latitudinal shifts of four ecologically important tree species between 1970 and 2014 within a study area that encompasses their northernmost range limit in northeastern North America (Quebec, Canada; ~761,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 68 publications
(115 reference statements)
2
37
2
Order By: Relevance
“…Our results contrast with those of Boisvert‐Marsh et al (), who found that climate was more important than disturbances in explaining tree sapling recruitment at their northern limit in Québec. This suggests that the pattern we uncovered might be caused primarily by an increase in abundance of species already present rather than by new colonization.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results contrast with those of Boisvert‐Marsh et al (), who found that climate was more important than disturbances in explaining tree sapling recruitment at their northern limit in Québec. This suggests that the pattern we uncovered might be caused primarily by an increase in abundance of species already present rather than by new colonization.…”
Section: Discussioncontrasting
confidence: 99%
“…As such, there is a growing body of evidence for contemporary shifts in tree species distributions along elevational gradients in mountains (Beckage et al, 2008;Lenoir, Gegout, Marquet, Ruffray, & Brisse, 2008;Savage & Vellend, 2015), where ecotones are narrow and well defined (Jump et al, 2009). Similar evidence is also beginning to emerge for latitudinal shifts (Boisvert-Marsh, Périé, & Blois, 2019;Fisichelli, Frelich, & Reich, 2014;Sittaro et al, 2017). However, because of the focus on shifts at range limits (e.g., leading and rear edges of species ranges), there has been little empirical work on the effect of climate change on tree community composition and abundance distributions within the core of the species range itself (e.g., Esquivel-Muelbert et al, 2018;Searle & Chen, 2017).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…This often involves a temporal mismatch between disturbances and the rate of climate change. First, if disturbances occur relatively infrequently, the effects of the shifting disturbance regimes may be minimal compared to shifting climatic variables (Boisvert‐Marsh, Périé, & de Blois, 2019). In other words, the velocity of climate change may be too fast and opportunities out of sync with life‐history constraints.…”
Section: When Do Disturbances Create Opportunities For Adaptation?mentioning
confidence: 99%